An Analysis of Illocutionary Act in Western Song Lyrics “Espresso By Sabrina Carpenter” - Valentine C.I. Letsoin; Khanna Maulidia ‘Ashr (Universitas Musamus Merauke, 2024)
This study aimed to investigate the illocutionary acts in the song lyrics of Sabrina Carpenter's